Diagnosis and management of asymptomatic bacteriuria in kidney transplant recipients: a survey of current practice in Europe. Issue 9 (9th April 2018) - Coussement, Julien; Maggiore, Umberto; Manuel, Oriol; Scemla, Anne; López-Medrano, Francisco; Nagler, Evi V; Aguado, José María; Abramowicz, Daniel
Abstract: Background: Asymptomatic bacteriuria is frequent in kidney transplant recipients (KTRs). However, there is no consensus on diagnosis or management. We conducted a European survey to explore current practice related to the diagnosis and management of asymptomatic bacteriuria in adult KTRs. Methods: A panel of experts from the European Renal Association–European Dialysis Transplant Association/Developing Education Science and Care for Renal Transplantation in European States working group and the European Study Group for Infections in Compromised Hosts of the European Society of Clinical Microbiology and Infectious Diseases designed this cross-sectional, questionnaire-based, self-administered survey. Invitations to participate were e-mailed to European physicians involved in the care of KTRs. Results: Two hundred and forty-four participants from 138 institutions in 25 countries answered the survey (response rate 30%). Most participants [72% (176/244)] said they always screen for asymptomatic bacteriuria in KTRs. Six per cent (15/240) reported never treating asymptomatic bacteriuria with antibiotics. When antimicrobial treatment was used, 24% of the participants (53/224) said they would start with empirical antibiotics. For an episode of asymptomatic bacteriuria caused by a fully susceptible microorganism and despite no contraindications, a majority of participants (121/223) said they would use a fluoroquinolone ( n  = 56), amoxicillin/clavulanic acid ( n  = 38) or oral cephalosporins ( n  = 27). Conclusions: Screening for and treating asymptomatic bacteriuria are common in KTRs despite uncertainties around the benefits and harms. In an era of antimicrobial resistance, further studies are needed to address the diagnosis and management of asymptomatic bacteriuria in these patients.